PENGHITUNG SETPOINT DOWN COUNTER OTOMATIS PADA LAMPU LALU LINTAS DENGAN MENGGUNAKAN PANEL LED DOT MATRIX - Galih Mustiko Aji; Purwiyanto Purwiyanto (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2017)
Down counter on the traffic light provides information for drivers on how long the lamps will be on or off, then they are not careless who can cause traffic jam and accidents. The instalation of down counter needs value of set point which derived from the traffic light controller or it is set manually by technician. The design of down counter which is capable of standing by itself, it is possible to use less cables and it will facilitate on its time changing and the maintenance of traffict light. In this research, a down counter which counts by itself will be create value of set point which designed by using display of let dot matrix panel with the size of 32x32 pixel. It is able to display figures as many as 2 digits of 99 until 00.